Mass spectrometry-from peripheral proteins to membrane motors. - Morgner, N; Montenegro, F; Barrera, N; Robinson, C (2012)
That membrane protein complexes could survive in the gas phase had always seemed impossible. The lack of chargeable residues, high hydrophobicity, and poor solubility and the vast excess of detergent contributed to the view that it would not be possible to obtain mass spectra of intact membrane complexes. With the recent success in recording mass spectra of these complexes, first from recombinant sources and later from the cellular environment, many surprising properties of these gas phase membrane complexes have been revealed. The first of these was that the interactions between membrane and soluble subunits could survive in vacuum, without detergent molecules adhering to the complex. The second unexpected feature was that their hydrophobicity and, consequently, lower charge state did not preclude ionization. The final surprising finding was that these gas phase membrane complexes carry with them lipids, bound specifically in subunit interfaces. This provides us with an opportunity to distinguish annular lipids that surround the membrane complexes, from structural lipids that have a role in maintaining structure and subunit interactions. In this perspective, we track these developments and suggest explanations for the various discoveries made during this research.